PENGELOLAAN PEMBELAJARAN FIQIH UNTUK MENINGKATKAN KEMAMPUAN INTERPERSONAL PESERTA DIDIK DI MTs AL-ISLAM MLARAK PONOROGO - Afifah, Nurul (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2015)
Learning management is the capacity of the teacher to design learning Â process. Through a good management, the learning will be achieved the desired Â learning objectives. There are three stages in the implementation of learning Â management namely design strategies and lesson planning, then management Â during the learning process, and the evaluation of learning outcomes. In the learning management, there are two goals to be achieved. The first is instructional effects, it means the objectives of teaching that explicitly sought accomplishments with specific actions. The second is nurturing effect, it means the goals that show bonding results. It can be achieved because the students are to live in a system of specific learning environment. Interpersonal intelligence as part of a nurturant effect, indispensable achievements. Because mastery of interpersonal intelligence, will be the students as personal understanding the felling, it can take the appropriate action, put yourself supple, harmonious and in tune with the social environment. The correlation between interpersonal intelligence and fiqih is the behavior of dynamic human activity by fiqihâs patterned after the valuesÂ Â Â that guarantee the establishment of a religious and pious society. This is a classroom action research research. Techniques of data collection method by observation, test and interviews. The data analysis tehniques used descriptive was exploratory. Implementation of this research is the learning management of fiqh in MTs. Al-Islam to improve interpersonal intelligence of the students, done in two ways. Firstly, by implementing cooperative learning strategies. It is intended that students can interact longer with their friends in the discussions and group work. Secondly, the various actions of the fiqih teacherâs in the classroom and outside the room. The results of interpersonal intelligence of the students in MTs. Al-Islam increase as well.Keywords: Learning Management, Fiqhâs learning, Interpersonal Intelligence.